Heminephrectomy for a large renal mass in a horseshoe kidney: A case report outlining a robotic assisted laparoscopic approach - Matthew Mancuso; Benjamin B. Beech; David W. Chapman; Blair St Martin (Laparoscopic, Endoscopic and Robotic Surgery, 2022)
With an incidence of 1/500, a horseshoe kidney is not uncommon. Tumours discovered in horseshoe kidney however are quite rare, and prove difficult to surgically manage due to complex vascular anatomy. With variable surgical approaches previously described, only a select few robot-assisted cases have been reported. This case describes one such robot-assisted laparoscopic heminephrectomy, with the use of indocyanine green and an endovascular stapler to successfully demarcate ischemia and achieve hemostasis intraoperatively. No complications were encountered, and pathology revealed a pT1bN0 clear cell renal cell carcinoma with negative surgical margins, demonstrating the feasibility of our approach.